The Myth of Beauty and Black Bodies - Moreno Gómez, Diana Katherine (2021)
This article presents reflections that allow us to analyze the concept of beauty linked to black bodies and the inclusion or exclusion they experience in this concept from the myth of beauty. It aims to address how the black appearance is perceived from the hegemonic structures, how the person perceives themselves and possible reasons for these perceptions. The myth of beauty is retaken as a political construction that has tried to perpetuate processes of female domination and how, through activism, black communities have politically configured a counterpart of the myth of beauty that is constituted in processes of black vindication, through of which it is possible to recognize, value and give rise to the historical construction that black women have made on gender.